2008
DOI: 10.1590/s0102-86502008000400003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of positive end-expiratory pressure in alveolar recruitment during mechanical ventilation in pigs

Abstract: PEEP adjusted to MAP of 20 cmH2O resulted in best arterial oxygenation, without compromising the venous return, as opposed to MAP of 25 cmH2O, which caused deterioration of gas exchange, hemodynamics and respiratory mechanic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…8,16 In the present study, we used 2 different levels of PEEP after unilateral lung transplant in pigs and demonstrated that mechanical ventilation with higher PEEP levels (10 cm H 2 O) using a pressure-controlled mode increased lung compliance and reduced airway resistance (Table 1). Higher PEEP was not associated with better oxygenation in pigs after unilateral lung transplant (Table 1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…8,16 In the present study, we used 2 different levels of PEEP after unilateral lung transplant in pigs and demonstrated that mechanical ventilation with higher PEEP levels (10 cm H 2 O) using a pressure-controlled mode increased lung compliance and reduced airway resistance (Table 1). Higher PEEP was not associated with better oxygenation in pigs after unilateral lung transplant (Table 1).…”
Section: Discussionmentioning
confidence: 59%
“…17,18 The present ventilatory findings were consistent with those from previous studies that evaluated the effects of increasing levels of PEEP at constant tidal volume, which resulted in higher compliance and lower resistance. 16 Experimental and clinical studies have shown that protective ventilatory strategies and open-lung strategies may affect the progression of lung injury. [19][20][21][22] The present histologic findings included severe acute lung injury in both groups after transplant and at the end of the observation period.…”
Section: Discussionmentioning
confidence: 99%